The Combination of Slow Deep Breathing and Qur’anic Murottal Therapy in Reducing Blood Pressure in Hypertension: A Case Study - Adellia Andria Puspita; Rohmah, Anis Ika Nur (Jurnal Kesehatan Metro Sai Wawai, 2025)
Hypertension is a non-communicable disease that often occurs without symptoms and is a leading cause of premature death. In addition to persistently elevated blood pressure, hypertensive patients frequently experience unstable blood pressure variability (BPV), both short- and long-term. While antihypertensive medications are effective, they often cause undesirable side effects. Therefore, a safe and practical non-pharmacological approach is needed, such as slow deep breathing techniques and Qur'anic murottal therapy. This study aims to explore the effect of combining slow deep breathing and Qur'anic murottal therapy on blood pressure in hypertensive patients. This research used a descriptive approach with a case study method involving one hypertensive patient who met the inclusion criteria, namely having a blood pressure >140/90 mmHg, no hearing impairment, and having provided informed consent. The intervention was carried out once daily for 30 minutes over three consecutive days. The intervention followed the SOP for slow deep breathing combined with Qur'an murottal therapy. Blood pressure was measured before and after each session. There was a consistent decrease in blood pressure, pulse rate, and respiratory rate over the three-day period. These findings suggest that the combined therapy promotes relaxation and lowers blood pressure. The stable reduction also indicates its potential in managing blood pressure fluctuations. Further research with a quantitative design and a larger sample size is recommended to strengthen the generalization of results and support the broader application of this therapy in various healthcare settings.